Analysis of the Role of the Drought-Induced Gene DRI15 and Salinity-Induced Gene SI1 in Alternanthera philoxeroides Plasticity Using a Virus-Based Gene Silencing Tool - Bai, Chao; Wang, Peng; Fan, Qiang; Fu, Wei-Dong; Wang, Le; Zhang, Zhen-Nan; Song, Zhen; Zhang, Guo-Liang; Wu, Jia-He (Frontiers in Plant Science, 2017)
Alternanthera philoxeroides is a notoriously invasive weed that can readily adapt to different environmental conditions. Control of this weed is difficult, and it spreads easily and causes damage to native habitats and agriculture. In this study, our goal was to investigate the molecular mechanisms that lead to the ability of A. philoxeroides to invade new habitats, to adapt to environmental stresses, and to cause damage. We developed a simple and highly effective potato virus X-based virus-induced gene silencing (VIGS) approach. The VIGS approach was first used to silence the phytoene desaturase gene, which resulted in the expected photo-bleaching phenotype. Next, the VIGS approach was used to silence two additional genes, drought-induced protein gene 15 (ApDRI15) and salinity-induced protein gene 1 (ApSI1). When ApDRI15 was knocked down, the plants were more sensitive to drought stress than the control plants, with smaller leaves, shorter internodes, and lower biomass. The ApDRI15-silenced plants had lower relative water content, lower free proline levels, and higher water loss rates than the control. Silencing of ApSI1 significantly decreased tolerance to salinity, and the ApSI1-silenced plants were withered and smaller. These results indicate that the pgR107 VIGS approach is a simple and highly effective tool for dissecting gene function in A. philoxeroides. Further experiments with the VIGS approach will enhance our understanding of the molecular mechanisms of the adaptability and plasticity of A. philoxeroides and improve our ability to combat the damage caused by this weed.